2019
DOI: 10.1038/s41427-018-0102-x
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation ferroelectric domain-wall memories: principle and architecture

Abstract: The downscaling of commercial one-transistor-one capacitor ferroelectric memory cells is limited by the available signal window for the use of a charge integration readout technique. However, the erasable conducting charged walls that occur in insulating ferroelectrics can be used to read the bipolar domain states. Both out-of-plane and in-plane cell configurations are compared for the next sub-10-nm integration of ferroelectric domain wall memories with high reliability. It is highlighted that a nonvolatile r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 19 publications
0
53
0
Order By: Relevance
“…Although conducting domain walls have already been analyzed and discussed more than half a century ago, only the recent in-depth studies have revealed their full technological potential and triggered world-wide interest. During the last decade, domain-wall-based multi-configurational devices, atomic-scale electronic components and memory technology have been proposed [58,112,113]. Another idea is to use domain walls in order to achieve reconfigurable doping: While semiconductor technology enables the precise control of charged dopants during the fabrication process, their location remains fixed.…”
Section: Conduction In Domain Wallsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although conducting domain walls have already been analyzed and discussed more than half a century ago, only the recent in-depth studies have revealed their full technological potential and triggered world-wide interest. During the last decade, domain-wall-based multi-configurational devices, atomic-scale electronic components and memory technology have been proposed [58,112,113]. Another idea is to use domain walls in order to achieve reconfigurable doping: While semiconductor technology enables the precise control of charged dopants during the fabrication process, their location remains fixed.…”
Section: Conduction In Domain Wallsmentioning
confidence: 99%
“…Then, doping may be achieved in ferroelectrics within the domain walls. For more insight into the physics and properties of ferroelectric domain walls, we refer to, e.g., the recent review articles by Catalan et al [55], Meier [54], Jiang et al [113], and Bednyakov et al [56].…”
Section: Conduction In Domain Wallsmentioning
confidence: 99%
“…Recently, the demand for the use of multiferroics in various fields and products of nanoelectronics has been growing steadily. One of the most interesting compounds in the form of a thin film is bismuth ferrite (BFO) because of its electric [ 1 ], magnetic [ 2 ], piezo [ 3 , 4 ], ferroelectric [ 5 ], dielectric [ 6 ], memristive [ 7 , 8 ] and optical [ 9 , 10 , 11 , 12 ] properties. In addition, BiFeO 3 /reduced graphene oxide composites have excellent photocatalytic characteristics due to improved light absorption, an increase in the number of reactive centers and a low rate of recombination of electron–hole pairs [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding domain wall memory, so far, simple two-terminal binary and multilevel domain wall devices show promising characteristics [3,175], although the question of whether they will be any better than (or can even compete with) existing technologies remains and needs to be addressed further. The main factors that can potentially determine this, but are yet to be critically explored, include the speed of operation, retention, energy consumption, and integration with existing semiconductor architectures [199]. Nevertheless, research on domain walls has seen considerable progress and interest over the last few years and lays the foundation for future research in this direction.…”
Section: Discussionmentioning
confidence: 99%